2016
DOI: 10.1016/j.marpolbul.2016.05.057
|View full text |Cite
|
Sign up to set email alerts
|

Source apportionment of polycyclic aromatic hydrocarbons (PAHs) in sediments from Khuzestan province, Iran

Abstract: a b s t r a c t Available online xxxxKhuzestan, Iran is heavily industrialised with petrochemical and refinery companies. Herein, sediment and soil samples were collected from Hendijan coast, Khore Mosa and Arvandroud River. The CHEMSIC (CHEmometric analysis of Selected Ion Chromatograms) method was used to assign the main sources of polycyclic aromatic hydrocarbon (PAH) pollution. A four-component principal component analysis (PCA) model was obtained. While principal component 1 (PC1) was related to the total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…As a developing country, Iran is profoundly exposed to environmental pollution caused by PAHs. Studies in Tehran (Karyab et al, 2013;Naddafi et al, 2017) and other large cities of Iran (Lübeck et al, 2016;Goudarzi et al, 2017) have confirmed that PAHs, which are abundant in smoke, contaminated air, and smoke from fossil fuels, are environmental pollutants. The human body has two protective mechanisms (i.e., the first and the second phases of antioxidant defense) to protect against these threatening compounds.…”
Section: Introductionmentioning
confidence: 96%
“…As a developing country, Iran is profoundly exposed to environmental pollution caused by PAHs. Studies in Tehran (Karyab et al, 2013;Naddafi et al, 2017) and other large cities of Iran (Lübeck et al, 2016;Goudarzi et al, 2017) have confirmed that PAHs, which are abundant in smoke, contaminated air, and smoke from fossil fuels, are environmental pollutants. The human body has two protective mechanisms (i.e., the first and the second phases of antioxidant defense) to protect against these threatening compounds.…”
Section: Introductionmentioning
confidence: 96%
“…They become a sink for a wide variety of low‐ to mid‐polarity organic contaminants and their degradation products [ 1 , 2 ]. Nonpolar compounds such as polycyclic aromatic hydrocarbons, polychlorinated biphenyls, and other persistent organic pollutants are routinely monitored in solid matrices using target workflows with GC‐MS or GC coupled to electron capture detectors [ 2 , 3 , 4 , 5 , 6 ]. Midpolar to polar compounds such as certain pharmaceuticals, and household or personal care products can be analyzed with UHPLC and high‐resolution MS [ 2 , 6 , 7 ] to avoid the use of derivatization in GC and allow the determination of non‐volatile and thermally labile compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Pixel-based analysis of sections of chromatograms is an especially interesting alternative to peak integration for forensic mid-distillate spill investigations, because the search for spill-source matching is done using all the potential chromatographic pixels, instead of only a few selected compounds susceptible to weathering. Christensen et al have already introduced the so-called CHEMSIC method (CHEMometric analysis of Selected Ion Chromatograms) for forensic investigations about crude oil environmental spills using 1D GC-MS. CHEMSIC provides important advantages compared to the conventional approach, such as (i) a more comprehensive diagnostics as a larger fraction of the chromatographic data is analyzed instead of only preselected target compounds, and (ii) higher flexibility in forensic investigations as tens of different SICs can be combined for the analysis …”
Section: Introductionmentioning
confidence: 99%